2017
DOI: 10.3847/1538-4357/834/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Mass of Compact Object in H 1743-322 From 2010 and 2011 Outbursts Using Tcaf Solution and Spectral Index–qpo Frequency Correlation

Abstract: The well known black hole candidate H 1743-322 exhibited temporal and spectral variabilities during several outbursts. Daily variation of the accretion rates and the flow geometry change on a daily basis during each of the outbursts could be understood very well using the recent implementation of two component advective flow (TCAF) solution of the viscous transonic flow equations as an additive table model in XSPEC. This has dramatically improved our understanding about the accretion flow dynamics. Most intere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 59 publications
2
55
0
Order By: Relevance
“…During our analysis, we found that the 2003 and part of 2004 (see also Bhattacharjee et al 2017) outbursts are very unsettling in the sense that either the model fitted parameters fluctuate on a daily basis as in the phenomenological diskbb plus power-law model or it is impossible to fit the data with TCAF which satisfactorily fitted other outbursts Molla et al 2017). Thus the disc structure is clearly non-steady and evolving.…”
Section: Comparison Among the Outbursts Of H1743-322mentioning
confidence: 90%
See 2 more Smart Citations
“…During our analysis, we found that the 2003 and part of 2004 (see also Bhattacharjee et al 2017) outbursts are very unsettling in the sense that either the model fitted parameters fluctuate on a daily basis as in the phenomenological diskbb plus power-law model or it is impossible to fit the data with TCAF which satisfactorily fitted other outbursts Molla et al 2017). Thus the disc structure is clearly non-steady and evolving.…”
Section: Comparison Among the Outbursts Of H1743-322mentioning
confidence: 90%
“…For the analysis, HeaSOFT package version 6.19 was used with XSPEC 12.9.0 (Arnaud 1996). We use TCAF model (local model with fits file TCAF v0.3.fits) following methods explained in greater details by Debnath et al (2014Debnath et al ( , 2015a; Mondal et al (2014Mondal et al ( , 2016; Molla et al (2016Molla et al ( , 2017; Jana et al (2016); Chatterjee et al (2016); Bhattacharjee et al (2017) to obtain fits of the spectra along with tbabs (Wilms et al 2000) to account for interstellar extinction. We take the fixed value of hydrogen column density at N H = 1.6 × 10 22 atoms cm −2 (Capitanio et al 2009).…”
Section: Observation and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Tursunov & Kološ (2018) found the mass (M) to be 11.2 M and spin to be 0.4 from the magnetic relativistic precession model to explain the twin high-frequency QPOs and low-frequency QPO. By fitting the spectrum using the two-component advective flow model and the spectral index versus QPO correlation, Molla et al (2017) estimated the mass of the compact object to be 11.21 +1.65 −1.96 M . Whereas Bhattacharjee et al (2017) constrained the mass of the black hole in the range of 10.31 M −14.07 M from spectral modelling and the evolution of the QPO frequency.…”
Section: Introductionmentioning
confidence: 99%
“…This black hole LMXB has undergone six outbursts since 2003 with the soft disc dominated state (considering up to 2015 May; Tetarenko et al (2016)), which we use for calculating the duty cycle (which is roughly ∼ 0.07). The mass of this black hole was determined to be 13.3 ± 3.2 M ⊙ by Shaposhnikov & Titarchuk (2007) Molla et al (2017) using 2010 and 2011 RXTE/PCA outburst data. But the mass of the secondary companion star is not known for this transient system.…”
Section: Alignment Time: H 1743-322mentioning
confidence: 99%